Molecular Characterization of Listeria monocytogenes from Raw Milk - Wong, Gwo Rong (Universiti Malaysia Sarawak, UNIMAS, 2013)
Listeria monocytogenes has been reported as causative agent of foodborne disease which had gain public health concern as it can cause listeriosis in human especially in pregnant women, immunocompromised adults and infants. Various studies on molecular characterization of L. monocytogenes in foods had been done in Malaysia such as chicken, beef and ready-to-eat foods. However, the study of L. monocytogenes in raw milk is still not well established. The objectives of this study were to detect, isolate and characterize the presence of L. monocytogenes from raw milk by using (GTG)5-PCR. Raw milk was collected from Kota Samarahan and Kuching, Sarawak, and it was transported to laboratory for analysis. Samples were enriched using Tryptone Soy Broth, then plated on PALCAM agar for isolation purposes. Next, the colonies formed on PALCAM agar were confirmed by species-specific PCR using LM1 and LM2 specific primer for detection of L. monocytogenes. The 234 bp hly gene was successfully amplified by PCR. Confirmed isolates were characterized molecularly using (GTG)5-PCR method with 15-mer primers, GTG. (GTG)5-PCR results were analysed using RAPDistance bioinformatics software. A dendrogram was successfully formed from (GTG)5-PCR binding pattern and genetic distribution of L. monocytogenes was obtained. Based on the study, 14 positives L. monocytogenes were successfully isolated and characterized using (GTG)5-PCR from the total of 120 isolates. Three clusters A, B and C showing the genetic distribution were formed from RAPDistance based on (GTG)5-PCR binding patterns. In conclusion, 14 L. monocytogenes isolates were detected, isolated and characterized into three clusters.